Estimate for a Rearrangement of a Function Satisfying the “Reverse Jensen Inequality” - Korenovskii, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We show that an equimeasurable rearrangement of any function satisfying the “reverse Jensen inequality” with respect to various multidimensional segments also satisfies the “reverse Jensen inequality” with the same constant.